Chest ultrasonography and X-ray may be perfectly integrated in patients management after thoracic surgery such as Shaq and Kobe - Chiappetta, Marco; Congedo, Maria Teresa; Smargiassi, Andrea; Nachira, Dania; Margaritora, Stefano (Journal of Thoracic Disease, 2019)
We read with very interest the review of Dr. Nooitgedacht and colleagues (1) regarding the available literature using chest ultrasonography (CU) in the management of surgically treated patients.